AI AND CLOUD INTEGRATION: TRANSFORMING CRM PRACTICES - Davinder Pal Singh, (INTERNATIONAL JOURNAL OF COMPUTER ENGINEERING AND TECHNOLOGY (IJCET), 2024)
This comprehensive article examines the transformative impact of artificial intelligence and cloud computing integration in Customer Relationship Management (CRM) systems, highlighting key technological advancements, implementation strategies, and business outcomes. The article, drawing from studies spanning multiple organizations across numerous countries, reveals significant improvements in operational efficiency, with AI-enhanced CRM systems demonstrating substantial enhancements in response times, first-contact resolution rates, and customer lifetime value. The article explores critical aspects, including cloud infrastructure capabilities, AI integration points showing remarkable accuracy in natural language processing, real-time data architectures handling massive event processing, and advanced security frameworks maintaining exceptional data integrity. Additionally, it addresses implementation challenges, organizational considerations, and future trends, particularly in edge AI, quantum computing, and IoT integration, providing a comprehensive roadmap for organizations pursuing digital transformation in customer relationship management.